Gerakan Seni Tari yang Digarap melalui Kebudayaan dan Tradisi Bekarang Ikan di Batang Hari - Afifah, Putri (YASIN, 2023)
The research discusses a Bekarang Ikan tradition which is a former culture of fishing in swamps and rice field waters by the Batanghari community during the dry season. This tradition and culture has become a hereditary activity and is also part of the livelihood of the community which is still carried out today. In their activities, people go down to the swamp or rice field waters together using makeshift tolls, such as trawls, wounds, nets and the like. These traditions and cultures become a source of refence and ideas that try to be visualized in the form of dance movements, which describe a tradition and culture of the community. Mutual cooperation, joy, and gratitude are reflected in this tradition and culture.